Cats in Palace Museum: A narrative of cultural heritage and empathy of youth - Guo, Yunjiao; Huang, Tianle; Luo, Qiuju (Frontiers in Psychology, 2022)
While research in heritage tourism tends to focus on cultural and anthropogenic motivations and drivers, this paper seeks to examine how social-media narration amidst a broader backdrop context in Chinese mass culture creates, perpetuates, and reinforce feline-focused narratives and practices amongst social media young followers. Drawing on text and image-based analyses of postings of cat sightings within the official Palace Museum account on a key Chinese microblog, this study reveals the application of three vital narrative strategies at work and corresponding empathic responses: ambassadorial, bounded and broadcast. The Palace Museum has achieved an enhancement of interaction and emotional exchange between the heritage of Palace Museum and youths and generated a process from attention to emotional engagement and eventually to emotional identification on the part of youths in their attitude toward the heritage of Palace Museum through the workings of three key narrative strategies on Chinese social media. In doing so, this research illuminates the potential of social media-based narratives and charismatic animals in the revitalisation of cultural heritage sites and the contributions of setting narrative strategies in engaging the younger audiences while also revitalizing the cultural heritage of the Palace Museum.